Counselling and Religious Experience: Life Changes of Former Corruption Convicts can be Specifying Religious Experiences - Supriyanto, Agus; Mulawarman, Mulawarman; Sunawan, Sunawan; Harahap, Fera Hayani (Universitas Islam Negeri Raden Intan Lampung, 2022)
Corruption is a corrupted character and appears in certain politicians. Mental corruption in developing countries requires harsh sanctions, although it doesn’t provide a deterrent effect to the emergence of other corruptors in Indonesia. Imprisonment sanctions as long as possible can provide a religious experience so that the emergence of life changes. This article aims to analyse the spiritual experiences that have changed the lives of former corrupt convicts. Documentation study through the analysis of youtube videos from interviews with former corruption convicts who just got out of prison. The research subject is one woman—qualitative analysis as the basis for the emergence of various dimensions of religious experience. The study results found three basic dimensions of the emergence of spiritual experiences affective, cognitive, and behavioural. Religious experience in the affective dimension changes life with a process of acceptance, awareness, regret/mistake, gratitude, and sincerity—spiritual expertise with a cognitive size through self-belief and life lessons that can change lives. Religious experience also raises behavioural dimensions so that individuals can control themselves, be confident, and dare to act. These three dimensions serve as provisions for policymakers to internalise the anti-corruption character.